Novel classifiers with clinical laboratory parameters for early detection of osteosarcoma. Issue 5 (8th January 2020) - Cao, Lin‐Lin; Chen, Zhaoming; Yue, Zhihong; Pei, Lin; Jia, Mei; Wang, Hui; Li, Tingting
Abstract: Background: Osteosarcoma (OS) is one of the most common malignant bone tumors. It is essential to explore early diagnostic indicators with high sensitivity and specificity due to the rapid progression and metastasis of OS and the poor survival of metastatic OS patients. However, a few indicators of diagnostic significance have been described. Methods: A total of 458 OS patients, 312 healthy individuals, and 228 patients with primary benign bone lesions were included. Logistic regression was performed on 46 clinical laboratory parameters to establish the diagnostic classifiers, which were evaluated by analysis of the receiver operating characteristic (ROC) curves. Results: We established three diagnostic classifiers, called C os for all ages, C los for low ages, and C hos for high ages, with clinical laboratory parameters to distinguish OS from healthy individuals. All classifiers showed better diagnostic performances than alkaline phosphatase (ALP) in the independent validation cohort. In addition, these classifiers had better ability than ALP to discriminate OS from primary benign bone lesions. Furthermore, C os, C los, and C hos had larger AUC than ALP to identify small‐size and early‐stage OS and could also detect ALP‐negative OS effectively. Conclusion: Our study suggests the potential of C os, C los, and C hos as non‐invasive biomarkers for early OS.